ZnFe2O4 multi-porous microbricks/graphene hybrid photocatalyst: Facile synthesis, improved activity and photocatalytic mechanism - Hou, Y.; Li, Xin Yong; Zhao, Q.; Chen, G. (2013)
Great efforts have been made recently to develop graphene-based visible-light-response photocatalysts and investigate their application in environmental field. In this study, a novel graphene-supported ZnFe2O4 multi-porous microbricks hybrid was synthesized via a facile deposition–precipitation reaction, followed by a hydrothermal treatment. The morphology, structure and optical properties of the hybrid were well characterized, indicating that an intimate contact between ZnFe2O4 microbricks and graphene sheets has been formed. The photocatalytic degradation of p-chlorophenol experiments indicated that the graphene-supported ZnFe2O4 multi-porous microbricks hybrid exhibited a much higher photocatalytic activity than the pure ZnFe2O4 multi-porous microbricks and ZnFe2O4 nanoparticles under the visible light irradiation (λ > 420 nm). The enhancement of photocatalytic performance could be attributed to the fast photogenerated charge separation and transfer due to the high electron mobility of graphene sheets, improved light absorption, high specific surface area as well as multi-porous structure of the hybrid. Photoluminescence and radicals trapping studies revealed the hydroxyl radicals were involved as the main active oxygen species in the photocatalytic reaction. The work could open new possibilities to provide some insights into the design of new graphene-based hybrid photocatalysts with high activity for environmental purification applications.